Robotic-Assisted Urologic Surgery in Infants: Positioning, Trocar Placement, and Physiological Considerations - Kim, Soo Jeong; Barlog, John S.; Akhavan, Ardavan (Frontiers in Pediatrics, 2019)
Pediatric robotic-assisted laparoscopic procedures are becoming increasingly common. They have been shown to be safe in younger patients, including infants. Successful adoption of robotic-assisted surgery in infants requires an understanding of the technical factors unique to this patient population. This review will delineate the specific considerations to safely perform robotic-assisted laparoscopic procedures in infants, including physiological changes associated with pneumoperitoneum in infants, positioning, trocar placement, and docking.